2019
DOI: 10.1002/jbmr.3756
|View full text |Cite
|
Sign up to set email alerts
|

Beclin1 Modulates Bone Homeostasis by Regulating Osteoclast and Chondrocyte Differentiation

Abstract: Autophagy (ATG), an important cellular recycling process whereby macromolecules or organelles are encapsulated by autophagosome and degraded upon merging with lysosome, has recently been shown to play an essential role in bone biology. However, the involvement of ATG in bone and bone‐related cells remains unclear. Here, we show that Beclin1, an ATG‐related protein involved in ATG initiation, plays a pivotal role in osteoclasts. ATG was activated during osteoclast differentiation in vitro. Beclin1 was enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 55 publications
2
78
0
Order By: Relevance
“…Notably, Beclin1 expression was correlated with the expression of osteogenic differentiation markers OCN, ALP and COL 1 in patients with OPLL. Consistently, a recent study reported that Beclin1 plays an important role in the differentiation of osteoclasts and chondrocytes [9]. To con rm the role of Beclin1 in broblasts, siRNA targeting Beclin1 was designed and used to downregulate the expression of Beclin1.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, Beclin1 expression was correlated with the expression of osteogenic differentiation markers OCN, ALP and COL 1 in patients with OPLL. Consistently, a recent study reported that Beclin1 plays an important role in the differentiation of osteoclasts and chondrocytes [9]. To con rm the role of Beclin1 in broblasts, siRNA targeting Beclin1 was designed and used to downregulate the expression of Beclin1.…”
Section: Discussionmentioning
confidence: 71%
“…Autophagy, a macromolecular degradation process, plays a pivotal role in the maintenance of cell differentiation [9]. Autophagy of osteocytes was rst con rmed by Zahm et al [10], and subsequent studies had reported that autophagic receptor and Unc-51 like autophagy activating kinase 1 (ULK1) had an important effect on the activity and differentiation of osteoblasts [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that autophagy is a key process in bone cells differentiation. It has been reported that autophagy can regulate osteoclast and chondrocyte differentiation [37], and protect BMMSCs from oxidative stress [38], which indicates that autophagy plays protective roles in maintaining bone homeostasis. Our previous study also showed that impaired autophagy triggers intracellular ROS-induced senescence in BMMSCs, which shifts cellular lineage commitment from osteoblasts to adipocytes, consequently leading to bone aging [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Adolph et al reported that mice with epithelial specific compromised UPR (XBP1) and autophagy function (ATG16L1) spontaneously developed severe CD-like transmural ileitis [182], accompanied with NF-κB overactivation-mediated intestinal inflammation. Several studies revealed regulation of autophagy on bone cell development and function, as well as the effects of autophagy on bone microenvironment are context-dependent [183][184][185][186][187]. Wu et al reported that IEC-specific VDR regulated ATG16L1 level at both transcriptional and translational level [188].…”
Section: Intestinal Barrier-regulated Bone Lossmentioning
confidence: 99%